Islam, Secularism, and Liberal Democracy - Tauseef Ahmad Parray (International Institute of Islamic Thought, 2010)
Islam, Secularism, and Liberal Democracy analyzes the theoretical relationship between religion and democracy, specifically Islam’s relationship with liberal democracy. It discusses the relationship between Islam, Muslim-majority societies (viz., Iran, Turkey, and Indonesia), and liberal democracy in a way that advances theory and practice regarding their relations and this relationship is the immediate focus of this study, and the conclusions have a much broader applicability in illuminating the theoretical relationship between religion, secularism, and democracy in general, and in contributing to the development of a liberal-democratic theory for Muslim societies in particular.